Технология искусственного осеменения телок в летних лагерях - Буров, В. А.; Burov, V. A.; Сизинцев, А. Г.; Sizintsev, A. G.; Корейба, Людмила Володимирівна; Koreyba, Ludmila; Koreyba, L. V.; Koreyba, Lyudmila Volodymyrivna; Koreyba, L.; Koreiba, L. V.; Coregba, L. V.; Чумак, Е. В.; et al. (Дніпропетровський ДАУ, 2004)
Современное молочное скотоводство требует ежегодной замены не менее 22-25 % коров за счет введения в стадо высокопродуктивных первотелок. Это возможно лишь при правильной организации всего комплекса мероприятий по выращиванию, содержанию, кормлению и организации искусственного осеменения телок. Правильная организация технологии выращивания и искусственного осеменения телок является залогом высокой продуктивности молочного стада. Modern dairy farming requires an annual replacement of at least 22-25% of cows due to the introduction of highly productive heifers in the herd. This is possible only with the proper organization of the whole set of activities for the cultivation, maintenance, feeding and organization of artificial insemination of heifers. The correct organization of technology of cultivation and artificial insemination of heifers is a guarantee of high productivity of a dairy herd.
Technology of artificial insemination of heifers in summer camps
Корейба Людмила Володимирівна https://orcid.org/0000-0002-8658-1779
Keywords: відтворення стада; herd reproduction; корови; cows; штучне запліднення; artificial insemination